Biophysical and socioeconomic factors influencing soil carbon stocks: a global assessment - Duarte Guardia, Sandra; Peri, Pablo Luis; Amelung, Wulf; Thomas, Evert; Borchard, Nils; Baldi, Germán; Cowie, Annette L.; Ladd, Brenton (Springer, 2021)
Científico